2002
DOI: 10.1006/mthe.2002.0702
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Retinal Neovascularization by Intraocular Viral-Mediated Delivery of Anti-angiogenic Agents

Abstract: Neovascularization characterizes diabetic retinopathy and choroidal neovascularization associated with age-related macular degeneration, the most common causes of severe visual loss in the developed world. Gene transfer to the eye using adeno-associated viral (AAV) vectors is a promising new treatment for inherited and acquired ocular diseases. We used an AAV vector with rapid onset and high levels of gene expression in the retina to deliver three anti-angiogenic factors (pigment epithelium-derived factor, tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(81 citation statements)
references
References 18 publications
3
78
0
Order By: Relevance
“…62 Similar promising results were obtained in the same mouse model of retinopathy of prematurity, using rAAV-2/1-carrying genes encoding for endostatin, tissue inhibitor of metalloproteinase-3 (TIMP-3) or PEDF. 63 For choroidal neovascularization (CNV), an rAAV-2/ 2pedf was intravitreally or subretinally injected in mice where the Bruch's membrane was ruptured with laser photocoagulation, a mice model of induced neovascularization. At 4-6 weeks after intraocular injection of rAAV2pedf, the area of CNV at the Bruch's membrane rupture sites had significantly decreased compared with the CNV area at rupture sites in eyes injected with rAAV-2/ 2gfp.…”
Section: Gene Transfer In Animal Models Of Retinal Degenerationmentioning
confidence: 99%
“…62 Similar promising results were obtained in the same mouse model of retinopathy of prematurity, using rAAV-2/1-carrying genes encoding for endostatin, tissue inhibitor of metalloproteinase-3 (TIMP-3) or PEDF. 63 For choroidal neovascularization (CNV), an rAAV-2/ 2pedf was intravitreally or subretinally injected in mice where the Bruch's membrane was ruptured with laser photocoagulation, a mice model of induced neovascularization. At 4-6 weeks after intraocular injection of rAAV2pedf, the area of CNV at the Bruch's membrane rupture sites had significantly decreased compared with the CNV area at rupture sites in eyes injected with rAAV-2/ 2gfp.…”
Section: Gene Transfer In Animal Models Of Retinal Degenerationmentioning
confidence: 99%
“…The angiostatic activities of ATF and endostatin have already been described in numerous tumor models. 10,11,13,15 This is the first time that AFT has been shown to have angiostatic activity in a model of retinal neovascularization. We showed that that local gene transfer and the expression of ATFHSA reduce retinal neovascularization by 78.1%.…”
Section: Discussionmentioning
confidence: 91%
“…In other studies, the inhibition of neovascularization by endostatin was of the same order (80%). 15 However, endostatin reduces angiogenesis by inhibiting different steps of the angiogenic process, such as endothelial cell proliferation, apoptosis and cell migration in response to VEGF. 21 In this model of retinal vascularization, VEGF plays a key role, as its expression is regulated during hyperoxia (downregulation) and hypoxia (upregulation).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neovascularization can be inhibited by adenovirus-mediated or rAAV-mediated expression of vascular endothelial growth factor inhibitors, such as the soluble vascular endothelial growth factor receptor (sFlt-1), [91][92][93] angiostatin 94 or endostatin. 95 The size of laser-induced choroidal neovascularization lesions can also be reduced by a zinc-finger transcription factor that upregulates PEDF expression when delivered by AAV2. 96 Adenovirus-mediated overexpression of PEDF inhibits retinal and choroidal neovascularization, and furthermore, is reported to induce regression of established new vessels.…”
Section: Vector-mediated Neuroprotection and Modulation Of Ocular Angmentioning
confidence: 99%